The Recommendation or the Adjudication Authority of the Ombudsman of the Republic of Indonesia - Musriza Musriza; Eddy Purnama; Mahfud Mahfud (Kanun Jurnal Ilmu Hukum, 2021)
This research investigates the Ombudsman recommendations as the improvement of the maladministration’s prevention and the efforts that against government agencies which do not implemented their duties. This juridical-normative research uses four kinds of approach like statute, historical, conceptual and comparative approach. The Ombuds-man’s existence after 19 years establishment can be said hasn’t fully work as that institution expectation. The responsibility to accept all complaint about maladminis-tration especially in public services just relied only by issues the recommendations about conclusions and suggestions. Ombudsman doesn’t has the authority to execute the result of their investigations, so that the rules of recommendation’s implementation are weak. The 2016-2020 period’s recommendation haven’t implemented optimal enough. Therefore, recommendations as the improvement of the maladministration’s prevention need to equalizing the perspective and detailed the implementation rules, so that a stronger legal protection about the position and also the function of its recommen-dations can be achieving prosperity.